Estimation of SARS-COVID antibody level in mother and newborn baby among mothers affected by covid during the antenatal period - Murali , Rithanya; Logaprabhu, Nandini; Vijayaraghavan , Jaya (Asian Journal of Medical Sciences, 2023)
Background: Severe acute respiratory syndrome-coronavirus-2 infection increases the incidence of severe coronavirus disease-19 (COVID-19) in pregnant women. An increased risk of stillbirth and problems such as preeclampsia, preterm birth, and neonatal intensive care unit hospitalization may be caused by COVID-19 during pregnancy which might lead to an increased risk of COVID-19 mortality, admission to an intensive care unit, and mechanical ventilation. Aims and Objectives: To estimate SARS-COVID antibody level in mother and newborn baby among mothers affected by covid during the antenatal period. Materials and Methods: This is a prospective cross-sectional study conducted at Sri Ramachandra Institute of Higher Education and Research from June 2021 to September 2021. A total of 30 women, affected with SARS-COVID during the antenatal period, confirmed with reverse transcription-polymerase chain reaction testing were included in this study. Blood samples were collected from mothers at the time of delivery and cord blood sample was used for antibody detection in mothers and neonates respectively. Results: Severe infection was noted in 5 women (16.6%) who required oxygen supplementations, and 2 of them required heparin therapy. Women with severe illness showed decreased antibody levels-total antibody (≤500–100%), and neutralizing antibody (≤1000–60%), but statistical significance was not proved. Hence, antibody levels did not correlate with the severity of illness. Conclusion: The current study has demonstrated that women who were pregnant during the COVID-19 pandemic had good knowledge, attitudes, and practices. It is thought that these positive aspects will be beneficial to expectant mothers who are going through pregnancy while still adhering to health protocols or advice from medical professionals on how to carry a pregnancy safely amid this COVID-19 epidemic.